Mapping the future of information technology as information sources for Public Library: the case of Kuala Lumpur Library / Nik Lokman Nik Ismail - Nik Ismail, Nik Lokman (2001)
For many public librarians at this time, developing IT as information sources seemed an impossible challenge. In the early nineties and during the economic recession period had not been a good time for public libraries. There have been cuts, more cuts and yet more cuts in their budget, services were struggling, book funds had been slashed and staff were under resource which also happened to every organization either from public or private sector. The sudden arrival of IT technology or the information superhighway or the internet with its need for infrastructure investment, staff training and building remodeling seemed a challenge too far. How on earth could libraries afford to develop all these kind of services when they were barely managing to deliver existing services? This study will foresee a few factors and issues which rise in various aspects in the management and users at KL Library. A study to the high level of unawareness between the management of KL Library and users, points to the need to organize workshops and Information Technology seminars so that both groups can better understand the structural and practices needed for a full blown implementation of IT in KL Library. An information management strategy should be well equipped and formulated with knowledge and comprehensive plans, keeping in view the positive and negative environmental aspect of IT in the future. With the changing scene and environment in IT industry, this paper seeks an overview perspective on several major issues and problems that the industry may face and the suggested actions and solutions to nurture the industry within the library environment.